PERAN PENYULUH PERTANIAN DALAM MEMBERDAYAKAN PETANI DI KOTA YOGYAKARTA - Kadarso; Fahmi Atha Kanaka; Untoro Hariadi; Rini Anggraeni; Putri Perdana (Fakultas Pertanian Universitas Janabadra, 2025)
This study aims to determine the role of agricultural extension workers and the priority of agricultural extension workers' activities in empowering farmers in the city of Yogyakarta. The method used is a combination of quantitative and qualitative approaches to produce more comprehensive, valid, reliable, and objective data. Each farmer group is made up of 5-7 farmers so that the total sample is 88 farmers. Data sources consist of primary and secondary data collected through observation, literature study, interviews, questionnaires, and documentation. Data analysis uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. Based on the results of this study, it shows that the success of extension workers in social and technical roles has been felt by farmers, but the dimensions of responsiveness and anticipation are critical aspects that still need to be strengthened in order to answer the dynamics of urban agriculture in Yogyakarta.